CHALLENGES IN ACCESS TO AND UTILIZATION OF REPRODUCTIVE HEALTH CARE IN PAKISTAN - Ali, Moazzam; Bhatti, Mohammad Ayaz; Kuroiwa, Chushi (Journal of Ayub Medical College Abbottabad, 2008)
Background: Pakistan’s maternal mortality rate is high, and adequate and timely emergency services could prevent most maternal deaths. A woman’s right to life-saving services of skilled health care providers in childbirth is undeniable. This paper examines factors restricting women’s access to emergency obstetric care services in Pakistan. Method: This cross-sectional survey on emergency obstetric care services collected information at the health facility level using UN process indicators. The study enrolled 170 health facilities from nineteen randomly selected districts in Punjab and NWFP. Results: Diverse factors limit women’s access to Emergency Obstetric Care (EmOC) services. EmOC services were unavailable in most health facilities surveyed. Staff absenteeism, geographic remoteness, delayed access, and ambulance shortages jeopardize the transferral of seriously ill patients to higher level care facilities. Cultural norms dictate that women should be examined by women doctors, whose dearth makes these services inaccessible. Conclusion: Many maternal deaths would be avoidable if EmOC health services were accessible. The geographic obstacles to timely access, poor hospital infrastructure, and high staff absenteeism rates require immediate attention. Health facilities’ working hours were inconsistent with the provision of around-the-clock essential services, depriving and endangering the lives of many in need. It is imperative to increase skilled female workers capable of managing EmOC problems through proper incentives. A focused approach at local levels through proper supervision, motivation, and management would unquestionably save women’s lives. Keywords: Maternal health, social access, women mobility, referral hospitals; EmOC services.